Metode STEAM sebagai Inovasi Pembelajaran IPS Di Era Abad 21 - Sari Ratnawati; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
The application of STEM-based learning is expected to increase the activeness of students in social studies subjects. STEM-based learning was chosen to solve problems systematically, with creativity in applying scientific principles. The STEAM method as Social Science Learning Innovation in the 21st Century Era is one method that can be used for learning various current and future sciences. A teacher must be able to create a process that is fun, contextual, effective, or optimally efficient so that students can play an active role in the learning process. The STEAM method is the basis for the method in the learning process to teach abilities that refer to the development of a comprehensive world of technology. Steam (science, technology, engineering, arts, match) is a collaboration between science and everyday life. The purpose of this research is to find out that the steam method will improve students' learning abilities. This type of research is a field research with a qualitative descriptive method. The subjects of this study were students of class VII C of Junior Hight School 4 Cilacap, totaling 32 students. Data collection techniques used are observation techniques, and documentation. While the data analysis technique is qualitative analysis to determine the increase in student learning activity.